A study on the corrosive effect of 7.5% nominal hydrogen peroxide in high-level disinfection and sterilization of dental burs - Cardones, Sylvia T.; Herrera, Judith D.; Magtanong, Danilo (Adviser).
Ideally, dental burs are to be disposed of after every patient, but due to financial constraints, especially in the Philippines, it is common practice to use liquid disinfectants and sterilants on dental burs. Since burs are to be used more than once, it is required that the liquid disinfectants and sterilant has minimum if not absence of corrosive effect while offering high-level anti-microbial activity. The aim of the study was to determine the corrosive effect of a new and promising new product called 7.5% Nominal Hydrogen Peroxide (SPOROX?). Thirty burs were immersed in water and were marked as the control group. Another thirty were immersed in 7.5% Nominal Hydrogen Peroxide and were marked as the experimental group. The two sets of burs were exposed to their respective solutions at three different contact times: 0 minute (before immersion), 30 minutes (after high-level disinfection) and 6 hours (after cold sterilization). After each contact time, the burs were observed under the Scanning Electron Microscope (SEM) for presence or absence of corrosion microtags. Corrosion diameters (in micrometers) and types were noted. Data gathered from the study show that there is evidence of corrosion for both experimental and control groups only after 6 hours of immersion (cold sterilization). The corrosion diameter range for the control group was 26.70-46.70p: while in the experimental group, the range is 20.00-26.70u. It was also observed that the control group exhibited pitting type of corrosion while the experimental group showed the erosion type of corrosion. The study concludes that there is a statistically significant difference in the mean of corrosion diameter ranges of the control and experimental group. The corrosion diameter range of 7.5% Nominal Hydrogen peroxide is less than that of water, proving it less corrosive.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus -- Sterilization